Pseudohyponatremia in a neuroblastoma patient with obstructive jaundice and review of literature. Issue 2 (2021) - Bassi, Marta; Manzitti, Carla; Montalto, Shana; Giglio, Serena; Conte, Massimo; Facco, Fabio; Amoroso, Loredana
No abstract available